2000
DOI: 10.1080/028418500127345488
|View full text |Cite
|
Sign up to set email alerts
|

Cranial epidural tuberculoma: A case report

Abstract: A 33-year-old patient with cranial epidural tuberculoma without history of tuberculosis is described. CT and MR imaging showed a lesion located on both sides of a right frontotemporal bone destruction with epidural extent. Except for a small necrotic core, the lesion enhanced intensely after contrast medium administration. Osteitis and subgaleal abscess were associated. The displaced dura mater delineated the epidural tuberculoma. Diagnosis was verified by histology and identification of Mycobacterium tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…7 Intraparenchymal granulomatous lesions and chronic meningitis are the most common forms of central nervous system tuberculosis. 1,8 The presentation of a tuberculoma as a dura-based mass is unusual. Bauer et al 7 reported a case with intracranial tuberculoma that was initially diagnosed as an en plaque meningioma.…”
Section: Discussionmentioning
confidence: 98%
“…7 Intraparenchymal granulomatous lesions and chronic meningitis are the most common forms of central nervous system tuberculosis. 1,8 The presentation of a tuberculoma as a dura-based mass is unusual. Bauer et al 7 reported a case with intracranial tuberculoma that was initially diagnosed as an en plaque meningioma.…”
Section: Discussionmentioning
confidence: 98%
“…In view of herniation syndrome, urgent surgical decompression of the lesion was performed, and the histopathology showed features of tuberculosis [ 15 ]. Other than the above cases, intracranial tuberculoma of the dura mater with or without bone destruction has been reported [ 16 , 17 ]. Also, dural-based soft tissue nodular mass with diffuse homogenous enhancement with prominent vasogenic oedema involving the underlying cerebral hemisphere was also reported [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] Tuberculomas that affect the brain tissue occur more often than those that involve the dura or skull bone. [ 4 , 5 , 16 , 17 ] Most of these patients are immunocompromised. [ 20 ] Intracranial tuberculomas frequently occur as a result of tuberculous infection originating elsewhere in the body through hematogenous spread; the lung is the most common site of origin.…”
Section: Introductionmentioning
confidence: 99%